2010
DOI: 10.2337/db09-1776
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Human β-Cell Proliferation and Engraftment Using a Single G1/S Regulatory Molecule, cdk6

Abstract: OBJECTIVEMost knowledge on human β-cell cycle control derives from immunoblots of whole human islets, mixtures of β-cells and non-β-cells. We explored the presence, subcellular localization, and function of five early G1/S phase molecules—cyclins D1–3 and cdk 4 and 6—in the adult human β-cell.RESEARCH DESIGN AND METHODSImmunocytochemistry for the five molecules and their relative abilities to drive human β-cell replication were examined. Human β-cell replication, cell death, and islet function in vivo were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 55 publications
8
145
1
5
Order By: Relevance
“…recent study has revealed that CDK6 is capable of driving human b-cell proliferation in vitro and also, it is able to increase human islet engrafment/proliferation in vivo. 35 The findings altogether indicate that inhibition of cyclin-dependent kinase (CDK) function, particularly of CDK4/6 and CDK2, via protein-protein interaction with p27 may exert a critical effect in maintaining normal adult human b-cell quiescence and thus downregulation of p27 levels in b-cells may play a key role in promoting adult human b-cell replication in vitro and in vivo. We have shown using INS-1 cells and isolated adult human islets that RNAimediated p27 depletion promotes b-cell proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…recent study has revealed that CDK6 is capable of driving human b-cell proliferation in vitro and also, it is able to increase human islet engrafment/proliferation in vivo. 35 The findings altogether indicate that inhibition of cyclin-dependent kinase (CDK) function, particularly of CDK4/6 and CDK2, via protein-protein interaction with p27 may exert a critical effect in maintaining normal adult human b-cell quiescence and thus downregulation of p27 levels in b-cells may play a key role in promoting adult human b-cell replication in vitro and in vivo. We have shown using INS-1 cells and isolated adult human islets that RNAimediated p27 depletion promotes b-cell proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that overexpression of cdk-6 and cyclin D1 in isolated human β-cells in vitro induced BrdU incorporation and Ki67 expression. 35,80 It will be important to determine whether there is concomitant cell cycle completion and an increase in β-cell number as suggested by transplantation studies.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…CDK6 has also been found to be essential for b cell proliferation in pancreas. [12][13][14] However, CDK6 overexpression has also been shown to reduce skin tumorigenesis and cell growth in fibroblasts. 15,16 Phosphorylation of transcription factors CDK4/6 cyclin D complexes phosphorylate transcription factors, such as forkhead box M1 (FOXM1), mothers against decapentaplegic homolog 2/3 (SMAD2/3), eyes absent homolog 2 (EYA2) and methylosome protein 50 (MEP50) (cofactor) to alter their functions.…”
Section: Introductionmentioning
confidence: 99%